Sectoral business cycle synchronization in the European Union - Afonso, António (2010)
This paper analyses sectoral business cycle synchronization in an enlarged European Union using annual data for the period 1980-2005. In particular, we try to identify which sector for each country is driving the aggregate output business cycle synchronization. Overall, the sectors that provide the most relevant contribution are Industry, Building and Construction, and Agriculture, Fishery and Forestry. In contrast, the Services sector, the largest one in terms of valued added share, shows a relative low business cycle synchronization and volatility, implying that it contributes only marginally to the aggregate output business cycle synchronization.